A study on international law and war crimes / Nadia Zulkefli, Narimah Nahalan and Nasrullah Anuar - Zulkefli, Nadia; Nahalan, Narimah; Anuar, Nasrullah (2007)
The main idea in setting out this project is to make a comparative study in the area of international law, in its effectiveness theoretically and practically, by comparing previous events which happens throughout the years-namely the occupation of Iraq and the trial in Nuremberg. These two situations are taken into the core of our research as both situations are a good example on when and how the original idea and principle of the creation of the international law had been breached. In setting out this project, various researches had been- made in regards to Nuremberg trials and Iraq in digging for the truth beneath the mask of international law. Apart from that, various comments and criticisms by scholars throughout the globe-namely professors of law and jurists had been compared upon, in regards to the latter subjects, from these opinions, we exclude anything that is of the view of politics and public, as both political and public views will not be appropriate in handling the subject of international law as the law deals more with technicalities rather than opinions of persons who in majority does not have a law background. Throughout this research, clarifications on international law regarding its effectiveness, and ineffectiveness in various areas of law would be achieved, and it is the main aim of this research in digging for the truth when it comes to theories and practices of the said law, and, whether or not the law would be effective as it is to be in handling previous and present cases. The conclusion of this research should include the questions on whether or not the law in practice is as efficient as it was claimed in its theory, and that contradicting view between theories and realities would be furthermore clarified.